The poem "¡dolor, dolor!, eterna vida mía" by José Martí through discourse analysis (Orkopata. Revista de Lingüística, Literatura y Arte, 2023)
The poems of José Julián Martí Pérez, popularly known as José Martí, demonstrate his poetic, philosophical and political side. Therefore, the objective of this work was to critically analyze and interpret the poem "pain, pain! my eternal life" by the aforementioned author. The methodological design used was hermeneutics. In the interpretation technique, the Discourse Analysis model was applied, for which the following categories of analysis were taken into account: a) textual dimension, b) enunciative, c) semiotic and d) pragmatic. The results show the possibility of reflection that the human being has, with the possibility of aspiring to improvement in life, despite the misfortunes due to life circumstances. It is concluded that the poem reflects how in the circumstantial feeling an introspection can be made in life, and the capacity of the human being, to understand, interpret and manage nature, as well as its phenomena, regardless of the social context.
Keywords: analysis; discourse; ethnography; hermeneutics; linguistics